The Effects of Syntactic Awareness to L2 Chinese Passage-Level Reading Comprehension - Zhou, Jing (Frontiers in psychology, 2022)
This study investigated the association between syntactic awareness and L2 Chinese passage-level reading comprehension among 209 Chinese as a second language adult-learners. The participants were administered a character knowledge test, a vocabulary knowledge test, a morphological awareness test, a grammatical judgment and correction test, a word order test, and two reading comprehension tests (multiple-choice questions and cloze test). Partial correlation analyses showed that the participants’ performance in two syntactic awareness tasks were significantly positively correlated with their passage-level reading comprehension. Multiple regression analyses revealed that syntactic awareness made a unique contribution to L2 Chinese reading even when the effects of age, major, gender, length of learning Chinese, character knowledge, vocabulary knowledge, and morphological awareness were controlled for. In addition, the word order knowledge had a stronger predicting power to L2 Chinese reading comprehension compared to the grammatical judgment/correction ability.